2005
DOI: 10.1016/j.bbamcr.2005.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mitochondrial respiratory chain structure and function by estrogens/estrogen receptors and potential physiological/pathophysiological implications

Abstract: It is well known that the biological and carcinogenic effects of 17beta-estradiol (E2) are mediated via nuclear estrogen receptors (ERs) by regulating nuclear gene expression. Several rapid, non-nuclear genomic effects of E2 are mediated via plasma membrane-bound ERs. In addition, there is accumulating evidence suggesting that mitochondria are also important targets for the action of estrogens and ERs. This review summarized the studies on the effects of estrogens via ERs on mitochondrial structure and functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
106
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(118 citation statements)
references
References 203 publications
6
106
0
6
Order By: Relevance
“…Consistently, extranuclear localization of both ERα and ERβ has been indicated Milner et al, 2005;Herrick et al, 2006). In fact, increasing evidence has demonstrated that ERβ are mainly localized extranuclearly Cammarata et al, 2004;Chen et al, 2004a;Yang et al, 2004;Chen et al, 2005;Herrick et al, 2006). (Gustafsson, 1999).…”
Section: Mitochondrial Localization Of Erβmentioning
confidence: 61%
See 2 more Smart Citations
“…Consistently, extranuclear localization of both ERα and ERβ has been indicated Milner et al, 2005;Herrick et al, 2006). In fact, increasing evidence has demonstrated that ERβ are mainly localized extranuclearly Cammarata et al, 2004;Chen et al, 2004a;Yang et al, 2004;Chen et al, 2005;Herrick et al, 2006). (Gustafsson, 1999).…”
Section: Mitochondrial Localization Of Erβmentioning
confidence: 61%
“…In recently years, estrogens have been appreciated as pleiotropic hormones that play roles in a wide variety of nonreproductive functions as cardiovascular function (Stevenson, 2000), memory and cognition (Sherwin, 1999), bone and mineral metabolism (Compston, 2001), and immune function (Ahmed et al, 1999). As indicated above, there is accumulating evidence suggesting that mitochondria are also important targets for the actions of estrogens (Chen et al, 2005;Felty and Roy, 2005)). Mitochondria play a fundamental role in cell respiration, through oxidative phosphorylation.…”
Section: Mitochondrial Localization Of Erβmentioning
confidence: 99%
See 1 more Smart Citation
“…The first receptors to be cloned, the endocrine nuclear hormone receptors, were discovered in an effort to define the mechanism of action of known hormones, such as: the amino-acid-derived thyroid hormone; the steroidal glucocorticoid, mineralocorticoid, and sex hormones; and the vitamins A and D. Several of these endocrine receptors, e.g. thyroid (TR), estrogen, (ER) and Vitamin D (VDR) receptors have established or emerging roles for influencing metabolic and mitochondrial function, reviewed elsewhere (Weitzel et al 2003;Chen et al 2005;Roy et al 2007). Subsequent to the molecular identification of classical endocrine receptors, additional members of the nuclear hormone receptor superfamily, so called "adopted orphan receptors", were discovered to respond with low-affinity to physiologic ligands derived from dietary and metabolic sources, such as bile salts, fatty acids and eicasanoids, present in concentrations (micromolar) orders of magnitude higher than classic endocrine hormones (nanomolar).…”
Section: Nuclear Hormone Receptorsmentioning
confidence: 99%
“…24 The mitochondrial genome encodes only 13 proteins that are part of the oxidative-phosphorylation complexes I, III, IV and V of the mitochondrial inner membrane. 25 Since most mitochondrial proteins are nuclear encoded, mechanisms for the biogenesis of mitochondria, the coordination of mitochondrial biogenesis with the cell cycle and the establishment/maintenance of the mitochondrial proteome have been intensively investigated. [26][27][28][29] Several mechanisms for protein trafficking involving mitochondria are known.…”
Section: Introductionmentioning
confidence: 99%